Keterlibatan Perempuan dalam Proses Pembentukan Peraturan Daerah tentang APBD di DPRD Kabupaten Barru - Yusriah Amaliah (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2017)
This study aims to determine the level of women's participation in the process of formulating local regulations on APBD in institutions legislative areas of Barru regency and influential fac-tors inside it. The research method used is qualitative research by parsing the data descriptively. Data collection technique done by observation, interview, literature study, as well as documentation using qualitative descriptive analysis techniques. The results of this study indicate that women's participation in the process of forming Regional Regulation of Regional Budget of Fiscal Year 2017 Regency Barru start from the design stage, discussion and determination yet optimal. This is seen in the process of discussion, the liveliness of members women in following the agenda of the hearing less though the trial running according to the specified groove. In quantity on essentially the needs of women and men are certainly different, for accommodate and understand women's issues as well formulating a policy is certainly more ideally if women are more active in the formulation. Women's participation in leadership government especially in the issue of the formation of local regulations on APBD are certainly influenced by some factors that support or inhibit. Supporting factors include policies related to women's opportunities, party involvement as a means communications, patriarchal culture, and Intra-intitial communication. Factor inhibitors include the quantity of women and capability of women to be involved in the process decision-making.